Awareness and Awakening: A Narrative-Oriented Inquiry of Undergraduate Students' Development of Mindful Agency in China - Wang, Qing; Law, Ho Chung; Li, Yan; Xu, Zhanfei; Pang, Weiguo (Frontiers in Psychology, 2017)
The article explores undergraduate students’ experiences of developing mindful agency as a positive learning disposition, their perceived change as a learner, and the possible impact of mindful agency coaching on students’ learning and personal growth, using a narrative research method. Seventy Chinese undergraduate students generated personal reflective journals and eight participants’ journals were selected to enter into the narrative-oriented inquiry. Our analysis revealed a number of primary themes based on which we produced a meta-story. The supplements of the story were exacted for further critical cross-case discussion. The finding indicated that the multifaceted development of mindful agency involved learning methods, emotional regulation, strategic thinking and awareness of planning, openness to experience, self-acceptance and self-esteem, and learning engagement, with enhanced sense of personal awareness and awakening. The coaching was supportive for students to foster positive self-identities and become more reflective, mindful and self-determined.